Successful use of extra-corporeal membrane oxygenation in a patient with streptococcal sepsis: a case report and review of literature - Pořízka, Michal; Kopecký, Petr; Prskavec, Tomáš; Kunstýř, Jan; Rulíšek, Jan; Balík, Martin (Prague medical report, 2015)
A young patient with streptococcal sepsis due to the phlegmon of his left thigh was admitted to the general intensive care unit. He developed a multi-organ failure and septic cardiomyopathy with subsequent cardiogenic shock. This resulted in hemodynamic instability unresponsive to conservative medical treatment. We report a successful application of veno-arterial extra-corporeal membrane oxygenation, which was used to overcome the period of critically low cardiac output caused by severe septic myocardial dysfunction.
Keywords: Streptococcal Infections; streptokokové infekce; mužské pohlaví; dospělí; Humans; Extracorporeal Membrane Oxygenation; Adult; septický šok; Shock, Septic; lidé; Male; mimotělní membránová oxygenace